SOSIALISASI MANFAAT BUNGA TELANG DAN PENGOLAHANNYA: KKN MAHASISWA UNIVERSITAS PGRI ADI BUANA DI DESA BETRO - Cholifah Tur Rosidah Tur Rosidah; Rosita ardivia; Ayu istiqomah; Dwi Riska Febrianti; Tito Budi; Sindi Berliyani; Nailussa'adah; Mifta adinda herliana Adinda Herliana (Universitas PGRI Adi Buana Surabaya, 2023)
Residents of Betro Village have potential in the form of many butterfly pea plants that thrive in every yard of their house. However, these beautiful flowers are only used as ornamental plants. Seeing this potential, Adi Buana PGRI University's KKN students took the initiative to conduct education or socialization as a whole regarding the benefits of butterfly pea flowers for health which can then also be processed into delicious food but still nutritious. Besides that, it is also able to provide new business opportunities and has the potential to generate additional economic income. The objectives of this activity include providing insight into the butterfly pea flower regarding its benefits, potential and processed food that can be produced. This service method integrates KKN-T activities and community service from tertiary institutions. The result of this service is that the women of Betro Village can understand more about the benefits, potential and processed food that can be produced from the butterfly pea flower, so they can have an independent business and come up with entrepreneurial ideas by utilizing the butterfly pea flower around them.